2016
DOI: 10.1039/c6ra01089j
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photo-degradation of bisphenol a under simulated solar light irradiation by Zn–Ti mixed metal oxides loaded on graphene from aqueous media

Abstract: In the present study, the mixed metal oxides (rGO-ZnTi-MMO-x, x presents weight percentage of GO) were obtained by thermal treatment of a Zn–Ti layered double hydroxides-graphene oxide (GO-ZnTi-LDHs) composite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There have been many studies on synthesizing ZnObased materials to decompose toxic organic substances in wastewater [9,[34][35][36][37], in which ZnO/TiO 2 and ZnO/rGO-rGH showed the effective materials of degrading BPA under UV irradiation [38,39]. However, the use of UV light can affect the ecosystem as well as it is much more expensive than using visible light.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on synthesizing ZnObased materials to decompose toxic organic substances in wastewater [9,[34][35][36][37], in which ZnO/TiO 2 and ZnO/rGO-rGH showed the effective materials of degrading BPA under UV irradiation [38,39]. However, the use of UV light can affect the ecosystem as well as it is much more expensive than using visible light.…”
Section: Introductionmentioning
confidence: 99%
“…ZnTi-mixed metal oxide (ZTM), which is one of these mixed metal oxides, has been used as a heterogeneous catalyst, in which the charge separation efficiency of photogenerated electron–hole pairs was improved within this intra heterojunction for enhancing the rate of reaction with high efficiency. ZnTiO 3 is an environmentally friendly and promising material for a variety of applications, including dehydrogenation reactions, microelectronics, optics, low temperature cofired ceramics, and potential photocatalysis. Different synthetic strategies, such as codoping, improved the photocatalytic activity of ZnTiO 3 perovskites toward applications in visible light regions . Niasari et al have reported that in the sol–gel method, the ZnTiO 3 photocatalyst has shown a high photocatalytic efficiency for methyl orange degradation under UV light.…”
Section: Introductionmentioning
confidence: 99%